Analisis Cluster Hasil Uji Kompetensi Lembaga Sertifikasi Profesi (LSP) Melalui Teknologi Data Mining - Raditya Danar Dana; Ahmad Faqih (STMIK IKMI Cirebon, 2020)
The implementation of the Competency Test at the LSP institution in higher education is an effort to ensure that students have abilities in certain fields according to predetermined competency standards. Education providers are required to always strive to improve the quality and quality of education with the aim that the student's academic performance will always improve. From the results of observations made in the research location, it was found a problem with the high number of failures in the implementation of the competency test. This study aims to conduct cluster analysis of the data resulting from the implementation of competency tests with the Data Mining approach through several stages in the form of data collection, data cleaning, data transformation, data modeling and data evaluation. This study resulted in grouping the results of competency tests which were divided into 3 clusters, namely cluster 1 as much as 38%, cluster 2 as much as 32% and cluster 3 as much as 30%..